Long-term Outcomes Improved with Column-Lengthening Procedures vs Arthroereisis - Rizzo, Toni (MD Conference Express, 2014)
Posterior tibial tendon dysfunction (PTTD) has a prevalence of 3% to 4% in the Western world. Selecting a management strategy for stage II PTTD is confusing because there are many recommended surgical procedures for this disorder. This article discusses a study comparing the clinical and radiologic outcomes of column-lengthening procedures with arthroereisis procedures.